2013
DOI: 10.4094/chnr.2013.19.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intensive Care Unit Nurses' Experience in Caring for Infants Who Are Dying.

Abstract: PURPOSE: The purpose of this phenomenological study was to explore neonatal intensive care unit (NICU) nurses' experience in caring for infants who are approaching death and to identity the meaning and structure of their experiences.METHODS: The participants were eight nurses who had experience in caring for these infants. In-depth interviews were performed from December, 2012 to February, 2013 until data were fully saturated. Collected data were analyzed using Colaizzi's method.RESULTS: Four theme clusters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…These results are very similar to those reported by Ko and Kim [18], and indicate that the nurses had a high ability to understand and express their own emotions and to understand and receive other's emotions, but were less able to utilize emotions for constructive activities and personal performance and to overcome and control psychologically disturbing situations. In a study by Kang and Bang [26] on NICU nurses' experiences with EOL infant care, many nurses reported that they did not know how to cope with grieving parents and that they responded passively. This could be seen as a lack of the ability to utilize or control emotions in psychologically disturbing situations, such as having to face death.…”
Section: Discussionmentioning
confidence: 99%
“…These results are very similar to those reported by Ko and Kim [18], and indicate that the nurses had a high ability to understand and express their own emotions and to understand and receive other's emotions, but were less able to utilize emotions for constructive activities and personal performance and to overcome and control psychologically disturbing situations. In a study by Kang and Bang [26] on NICU nurses' experiences with EOL infant care, many nurses reported that they did not know how to cope with grieving parents and that they responded passively. This could be seen as a lack of the ability to utilize or control emotions in psychologically disturbing situations, such as having to face death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, newly graduated nurses visited patients less frequently during end-of-life care, 24 and neonatal intensive care unit nurses compartmentalized their emotions and mentally focused on work when caring for terminally ill patients. 25 In addition, nurses experienced more emotional distress when a critically ill patient was young or the nurse had developed a close relationship with them. 26 Similarly, most current participants also tried to avoid the death of patients if they had been close to them.…”
Section: Coping With Psychological Burdenmentioning
confidence: 99%
“…④ 자신과 가족을 생각하며 자신의 삶을 반추하는 것 이다 (6,10). ⑤ 인간 삶과 죽음을 성찰하고 인간 존엄을 실천하는 것이다 (7,31,32). ⑥ 임종을 의연하게 바라보며 삶을 통찰하고 성장한 다 (7,9,28,30).…”
Section: ) 잠정적 기준 목록unclassified
“…③ 의연하게 바라보기 (7,9,21,28,30) ④ 인간 존엄 실천하기 (7,10,21,31,32) 본 연구를 통해 확인된 속성을 바탕으로 간호사의 환 자죽음 수용이란 '환자죽음을 경험한 간호사가 애도를 통해 도달하는 단계로써 자신의 삶을 반추해서 삶과 죽 음에 대한 통찰력을 얻고, 환자죽음을 의연하게 바라보 며 인간 존엄을 간호 현장에서 실천하는 것'으로 정의 하였다.…”
Section: 30-32)unclassified
See 1 more Smart Citation